The multifaceted functions of long non-coding RNA HOTAIR in neuropathologies and its potential as a prognostic marker and therapeutic biotarget - Faraz Ahmad; Ravi Sudesh; Atheeq Toufeeq Ahmed; Mohanapriya Arumugam; Darin Mansor Mathkor; Shafiul Haque (Expert Reviews in Molecular Medicine)
Long non-coding RNAs (lncRNAs) are progressively being perceived as prominent molecular agents controlling multiple aspects of neuronal (patho)physiology. Amongst these is the HOX transcript antisense intergenic RNA, often abbreviated as HOTAIR. HOTAIR epigenetically regulates its target genes via its interaction with two different chromatin-modifying agents; histone methyltransferase polycomb-repressive complex 2 and histone demethylase lysine-specific demethylase 1. Parenthetically, HOTAIR elicits trans-acting sponging function against multiple micro-RNA species. Oncological research studies have confirmed the pathogenic functions of HOTAIR in multiple cancer types, such as gliomas and proposed it as a pro-oncological lncRNA. In fact, its expression has been suggested to be a predictor of the severity/grade of gliomas, and as a prognostic biomarker. Moreover, a propound influence of HOTAIR in other aspects of brain heath and disease states is just beginning to be unravelled. The objective of this review is to recapitulate all the relevant data pertaining to the regulatory roles of HOTAIR in neuronal (patho)physiology. To this end, we discuss the pathogenic mechanisms of HOTAIR in multiple neuronal diseases, such as neurodegeneration, traumatic brain injury and neuropsychiatric disorders. Finally, we also summarize the results from the studies incriminating HOTAIR in the pathogeneses of gliomas and other brain cancers. Implications of HOTAIR serving as a suitable therapeutic target in neuropathologies are also discussed.